АЛКОГОЛЬНАЯ БОЛЕЗНЬ ПЕЧЕНИ. ЧАСТЬ 2 - Е. Ю. Еремина (Архивъ внутренней медицины)
The article represents contemporary data on the illness development mechanisms, the main disease manifestation forms and the treatment methods of the alcoholic liver disease. It also covers the disease progression reasons and the main risk factors.